Altered serum elements, antioxidants, MDA, and immunoglobulins are associated with an increased risk of seborrheic dermatitis. Issue 3 (March 2021) - Jahan, Ishrat; Islam, Md. Rabiul; Islam, Md. Reazul; Ali, Rubaiya; Rahman, S.M. Matiur; Nahar, Zabun; Hasnat, Abul; Islam, Md. Saiful
Abstract: Background: The exact mechanism for the pathophysiology of seborrheic dermatitis (SD) remains unknown. According to past knowledge, neuropsychiatric disorders, weak immune responses, fungal infections, antioxidants deficiencies, and inadequate nutrition might involve in SD. Here we evaluated serum trace elements, micronutrients, antioxidants, malondialdehyde (MDA), and immunoglobulins in SD patients. Methods: This case-control study recruited 75 SD patients and 76 age-and sex-matched healthy controls (HCs). We measured serum micronutrients using atomic absorption spectroscopic methods. Similarly, we assessed serum antioxidants applying the RP-HPLC techniques. Also, serum MDA and immunoglobulins levels were evaluated by UV-spectrophotometric and turbidimetric methods, respectively. Results: We observed higher serum levels of copper, manganese, iron, calcium, magnesium, and MDA in SD patients than HCs. Together with vitamin E, we noticed lower serum concentrations of immunoglobulin A, G, and M in SD patients than HCs. The present study detected a positive correlation between serum zinc and calcium levels (r = 0.365, p = 0.009) in SD patients. However, we identified a negative correlation between serum copper and calcium levels (r = -0.298, p = 0.035). Conclusion: The present study suggests that the altered levels of micronutrients, antioxidants, MDA, and immunoglobulins are associated with the pathophysiology of SD. These changes may not be the cause but the consequences of the disease. These findings might help to understand the etiopathology and management of SD. Abstract : Seborrheic dermatitis; Trace elements; Micronutrients; Antioxidants; Malondialdehyde; Immunoglobulins.